2011
DOI: 10.1182/blood-2010-09-310888
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR blocks the anti-inflammatory effects of glucocorticoids in myeloid immune cells

Abstract: A central role for the mammalian target of rapamycin (mTOR) in innate immunity has been recently defined by its ability to limit proinflammatory mediators. Although glucocorticoids (GCs) exert potent anti-inflammatory effects in innate immune cells, it is currently unknown whether the mTOR pathway interferes with GC signaling. Here we show that inhibition of mTOR with rapamycin or Torin1 prevented the anti-inflammatory potency of GC both in human monocytes and myeloid dendritic cells. GCs could not suppress nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 49 publications
5
112
2
1
Order By: Relevance
“…As reported, S6K1 and 4E-BP are the downstream effectors of TOR in humans [72], and Guertin et al [73] found that TOR activates S6K1 and inhibits 4E-BP expression in Drosophila. In human monocytes, TOR increases production of the anti-inflammatory cytokines IL-10 [74]. In the present study, compared with low or high levels of protein, optimal levels of dietary protein led to the up-regulation of TOR and S6K1 mRNA levels and to the down-regulation of 4E-BP1 and 4E-BP2 mRNA levels in the gills of grass carp.…”
Section: Optimal Level Of Dietary Protein Attenuated Inflammatory Ressupporting
confidence: 48%
“…As reported, S6K1 and 4E-BP are the downstream effectors of TOR in humans [72], and Guertin et al [73] found that TOR activates S6K1 and inhibits 4E-BP expression in Drosophila. In human monocytes, TOR increases production of the anti-inflammatory cytokines IL-10 [74]. In the present study, compared with low or high levels of protein, optimal levels of dietary protein led to the up-regulation of TOR and S6K1 mRNA levels and to the down-regulation of 4E-BP1 and 4E-BP2 mRNA levels in the gills of grass carp.…”
Section: Optimal Level Of Dietary Protein Attenuated Inflammatory Ressupporting
confidence: 48%
“…Rapa enhanced inflammatory cytokine production in macrophages via enhancing NF-kB and blocking STAT3 activity 27,28 . Rapa significantly blocked the anti-inflammatory effects of glucocorticoids in myeloid immune cells including monocytes and DCs 29 . Rapa treatment enriched NF-kB-related proinflammatory expression pathways and monocyte lineagespecific transcripts in kidney-transplanted recipients 30 .…”
Section: Discussionmentioning
confidence: 96%
“…The reason for this inconsistency is possibly due to the different cell types used. Previous study showed that long-term treatment with Rapa (1 h then followed by LPS stimulation for another 24 h) promotes peripheral blood mononuclear cells to produce more IL-1b in culture supernatants 25 . We also observed the inhibition of mTORC1 by Rapa (48 h) or deletion of mTOR almost completely rescued the pro-IL-1b expression at the mRNA and protein levels in TSC1 KO macrophages, inferring that mTORC1 inhibited pro-IL-1b production indirectly and blocking mTORC1 pathway facilitated its synthesis.…”
Section: Tsc1 Regulates Il-1b T Yang Et Almentioning
confidence: 99%
“…The involvement of mTOR pathway in the regulation of and IL-1b expression has been studied in mouse and human macrophages 22,25,26 . In the present study, using TSC1-deficient macrophages and macrophage cell lines, we studied the role of TSC1 on pro-inflammatory cytokine IL-1b expression and explored the associated molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%